Modified carbonaceous coal gangue and modification method thereof

The carbonaceous coal gangue is modified by water glass and modified polyvinyl acetate emulsion, which solves the problem of insufficient strength of carbonaceous coal gangue in concrete, and achieves the effect of improving its mechanical properties and expanding application.

CN119591336AActive Publication Date: 2025-03-11CHANGAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411574662.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-11
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The application of carbonaceous coal gangue in concrete is limited by its low strength and complex composition, which leads to its limitation in its promotion and utilization in concrete.

Method used

By modifying carbonaceous coal gangue with water glass and modified polyvinyl acetate emulsion, the chemical reaction between coal gangue and water glass is stimulated, forming an aluminosilicate gel to fill the pores of coal gangue, and chemical bonding is formed through the reaction between polyvinyl acetate emulsion and the surface of coal gangue, thereby improving the adhesion and mechanical strength of coal gangue.

Benefits of technology

It improves the mechanical properties of carbonaceous coal gangue in concrete, enhances compressive strength and flexural resistance, and expands its application in concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121473600000061
    Figure BDA0005121473600000061
  • Figure BDA0005121473600000071
    Figure BDA0005121473600000071
Patent Text Reader

Abstract

The invention relates to the field of cement concrete, and particularly discloses modified carbonaceous coal gangue and a modification method thereof. The modified carbonaceous coal gangue is prepared from the following raw materials in parts by weight: 1.5 to 3 parts of water glass, 5 to 8 parts of modified polyvinyl acetate emulsion, 20 to 30 parts of carbonaceous coal gangue and 2 to 4 parts of sulfate solution, and the modified polyvinyl acetate emulsion is obtained by copolymerization modification of methyl methacrylate and vinyl acetate emulsion; the preparation method comprises the following steps: pretreating the carbonaceous coal gangue, crushing, screening, cleaning, sequentially adding the water glass and the sulfate solution while stirring, continuously stirring for 5-10 minutes, slowly adding the modified polyvinyl acetate emulsion, stirring, uniformly mixing, and drying to obtain the modified carbonaceous coal gangue. The problem that the coal gangue concrete is poor in strength is solved, the prepared coal gangue concrete has high compressive strength and breaking strength, and the performance limitation of traditional coal gangue concrete is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete, and more specifically, to a modified carbonaceous coal gangue and a modification method thereof. Background Art

[0002] Coal gangue is a kind of solid waste that is inevitably produced in the process of coal mining and selection. It is mainly composed of rocks, mineral impurities, coal fragments, etc. Due to its complex composition and low strength, the traditional treatment method is mostly landfill or stacking, which not only occupies a lot of land, but also may cause environmental pollution. However, with the improvement of environmental protection and resource utilization awareness, how to effectively utilize coal gangue has become a research hotspot.

[0003] The application of coal gangue in concrete manufacturing is an effective attempt to recycle resources. However, since coal gangue is loose and porous and has low strength, especially the carbon content in carbonaceous coal gangue is higher than that of general coal gangue, its composition is complex, and the strength of the aggregate obtained after processing is not as good as natural stone, the use effect is not good, which limits the promotion and utilization of carbonaceous coal gangue in concrete. Summary of the invention

[0004] In order to improve the strength of carbonaceous coal gangue and increase the utilization rate of carbonaceous coal gangue in concrete, the present application provides a modified carbonaceous coal gangue and a modification method thereof.

[0005] In the first aspect, the present application provides a modified carbonaceous coal gangue, which adopts the following technical solution: A modified carbonaceous coal gangue comprises the following raw materials in parts by weight: 1.5-3 parts of water glass, 5-8 parts of modified polyvinyl acetate emulsion, 20-30 parts of carbonaceous coal gangue, and 2-4 parts of sulfate solution. The modified polyvinyl acetate emulsion is obtained by copolymerization and modification of methyl methacrylate and vinyl acetate emulsion.

[0006] By adopting the above technical solution, water glass can stimulate the chemical reaction of coal gangue to produce aluminosilicate gel and fill the pores of coal gangue. This chemical substance has a bonding effect, which can strengthen the adhesion between coal gangue and other raw materials used in concrete, which is beneficial to its performance improvement. At the same time, polyvinyl acetate emulsion reacts with hydroxyl groups or other active groups on the surface of coal gangue through emulsion polymerization to form chemical bonds. The emulsion can form a strong bonding layer on the surface of coal gangue, offsetting part of the negative effects of coal gangue aggregates, and improving the interfacial properties and mechanical strength of coal gangue. The polyvinyl acetate emulsion is further modified by methyl methacrylate to introduce rigid segments into polyvinyl acetate, thereby increasing the hardness of the modified polyvinyl acetate after curing, thereby further increasing the strength of coal gangue.

[0007] Optionally, the modified polyvinyl acetate emulsion is prepared by the following steps: Vinyl acetate, methanol, initiator and emulsifier are added in sequence and stirred evenly at room temperature. After heating to 60-70°C, methyl methacrylate is added. Polymerization reaction is carried out at normal pressure for 1-2 hours. The product is taken out and distilled to remove methanol to obtain modified polyvinyl acetate emulsion.

[0008] By adopting the above technical scheme, the polymerization conditions are mild. Methyl methacrylate is a monomer with relatively high hardness. When polyvinyl acetate is modified by methyl methacrylate, the rigid chain segments of methyl methacrylate will be introduced into the chain segments of polyvinyl acetate emulsion to form a copolymer, thereby improving the hardness of the modified polyvinyl acetate. In addition, the introduction of methyl methacrylate can also improve the wettability and spreadability of the copolymer, so that the modified polyvinyl acetate can adhere to the surface of coal gangue more evenly and tightly, thereby improving the hardness and stability of the coal gangue.

[0009] Optionally, in the preparation process of the modified polyvinyl acetate emulsion, the weight ratio of vinyl acetate, methyl methacrylate, emulsifier and initiator added is 2-4:1:0.2:0.3-0.5.

[0010] By adopting the above technical scheme and using methanol with a smaller solvent transfer constant as the solvent, it is easier to dissipate heat and control temperature to avoid local overheating. The viscosity of the system is low. Under certain reaction conditions, the reaction rate is controlled to obtain a modified polyvinyl acetate emulsion with a narrow relative molecular weight distribution. The emulsion has high stability, better wettability and adhesion to coal gangue, and adheres to the surface of coal gangue to help improve the strength of the coal gangue.

[0011] Optionally, the initiator is hydrogen peroxide.

[0012] By adopting the above technical solution, when the free radical of hydrogen peroxide is connected to the vinyl acetate monomer, an initiation effect is generated, resulting in the rearrangement of double bond electrons, transferring the active point to the vinyl acetate monomer, and initiating monomer polymerization. The selection of hydrogen peroxide due to its mild decomposition characteristics helps to control the rate of the polymerization reaction, which is conducive to the generation of a modified polyvinyl acetate emulsion with a narrow molecular weight distribution.

[0013] Optionally, the sulfate solution is any one of calcium sulfate and magnesium sulfate solution.

[0014] By adopting the above technical scheme, any one of calcium sulfate and magnesium sulfate solutions is used as an activator to accelerate the chemical reaction between water glass and coal gangue, promote the formation of aluminosilicate gel, fill the pores of coal gangue, and thus improve the density and strength of coal gangue.

[0015] Optionally, the raw materials further include 3-5 parts of active powder, and the active powder is any one of fly ash, limestone powder and silica fume.

[0016] By adopting the above technical solution, the active powder has a smaller particle size, a part of which can be filled in the pores of loose and porous coal gangue to improve the strength of the coal gangue, and the other part is adsorbed on the surface of the coal gangue to form aggregate, thereby improving the reactivity of the coal gangue. Therefore, when the coal gangue is applied to concrete, it can have better interaction with other raw materials and improve compatibility.

[0017] In a second aspect, the present application provides a method for preparing modified carbonaceous coal gangue, which adopts the following technical solution: A method for preparing modified carbonaceous coal gangue comprises the following steps: The carbonaceous coal gangue is pretreated, crushed, screened and cleaned, and then water glass and sulfate solution are added in sequence while stirring. After continuing to stir for 5-10 minutes, the modified polyvinyl acetate emulsion is slowly added, stirring is maintained, and the mixture is evenly mixed and then dried to obtain the modified carbonaceous coal gangue.

[0018] By adopting the above technical solution, the additives are fully in contact with the coal gangue through continuous stirring during the preparation process and are evenly distributed on the surface of the coal gangue particles, which is beneficial to the reaction between water glass, sulfate and modified polyvinyl acetate emulsion and the coal gangue, thereby improving its strength.

[0019] In a third aspect, the present application provides the application of modified carbonaceous coal gangue in concrete.

[0020] In summary, this application has the following beneficial effects: 1. Since the present application adopts water glass and polyvinyl acetate emulsion to modify the carbonaceous coal gangue, the internal pores of the carbonaceous coal gangue are effectively filled, thereby improving the mechanical properties of the carbonaceous coal gangue in concrete applications, and obtaining modified carbonaceous coal gangue concrete with high compressive strength and good flexural properties, thereby expanding the application of carbonaceous coal gangue.

[0021] 2. In the present application, polyvinyl acetate emulsion is preferably used, which can react with the surface functional groups of carbonaceous coal gangue to form chemical bonds, thereby improving the interface compatibility between coal gangue and other raw materials. When carbonaceous coal gangue is used in the concrete preparation process, it has good interface compatibility, thereby improving the mechanical properties of the overall material.

[0022] 3. The present application preferably uses modified polyvinyl acetate modified with methyl methacrylate, which combines the advantages of polyvinyl acetate emulsion and methacrylate, further improves the bonding strength between polyvinyl acetate emulsion and coal gangue, and the rigid chain segments of methacrylate will be introduced into the chain segments of polyvinyl acetate emulsion to form a copolymer, thereby increasing the hardness after curing, thereby increasing the overall strength of coal gangue. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0025] The loose bulk density of the carbonaceous coal gangue selected in this application is 1200-1400kg / m 3 , crushing value 10.0%.

[0026] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified polyvinyl acetate emulsion, the preparation of which comprises the following steps: 10 kg of vinyl acetate, 5 kg of methanol, 0.75 kg of initiator, and 0.5 kg of emulsifier were sequentially added to a polymerization kettle, the temperature was raised to 65°C, 2.5 kg of methyl methacrylate was added, and the polymerization was carried out at normal pressure for 1.5 hours, and the product was distilled at 70°C to remove methanol to obtain a modified polyvinyl acetate emulsion. The emulsifier was sodium dodecyl sulfate, and the initiator was ammonium persulfate.

[0027] Preparation Example 2 A modified polyvinyl acetate emulsion, the preparation of which comprises the following steps: 10 kg of vinyl acetate, 5 kg of methanol, 2 kg of initiator, and 0.5 kg of emulsifier were added to a polymerization kettle in sequence, the temperature was raised to 60°C, 5 kg of methyl methacrylate was added, and the polymerization reaction was carried out at normal pressure for 2 hours, and the product was distilled at 70°C to remove methanol to obtain a modified polyvinyl acetate emulsion. The emulsifier was sodium dodecyl sulfate, and the initiator was ammonium persulfate.

[0028] Preparation Example 3 A modified polyvinyl acetate emulsion, the preparation of which comprises the following steps: 10 kg of vinyl acetate, 5 kg of methanol, 1.75 kg of initiator, and 0.5 kg of emulsifier were sequentially added to a polymerization kettle, the temperature was raised to 70°C, 3.5 kg of methyl methacrylate was added, and the polymerization was carried out at normal pressure for 2 hours, and the product was distilled at 70°C to remove methanol to obtain a modified polyvinyl acetate emulsion. The emulsifier was sodium dodecyl sulfate, and the initiator was ammonium persulfate.

[0029] Preparation Example 4 A modified polyvinyl acetate emulsion is different from Preparation Example 1 in that the initiator used in this Preparation Example is hydrogen peroxide. Example

[0030] Example 1 A modified carbonaceous coal gangue, the preparation of which comprises the following steps: Take 20kg of carbonaceous coal gangue for pretreatment, crush the carbonaceous coal gangue to a particle size of less than 4.75mm, screen, wash with water, put it into a blender and stir, add 3kg of water glass and 3kg of calcium sulfate in sequence, continue stirring for 10min, slowly add 8kg of modified polyvinyl acetate emulsion, keep stirring for 5min, mix well, and naturally dry to obtain modified carbonaceous coal gangue. The modified polyvinyl acetate emulsion used in this example is prepared in Preparation Example 1.

[0031] An application of modified carbonaceous coal gangue in concrete is as follows: 15 kg of modified carbonaceous coal gangue, 20 kg of cement, 5 kg of quartz sand and 10 kg of water heated to 50 ° C were added to the mixer in sequence. After stirring for 3 minutes, 0.8 kg of polycarboxylic acid water reducer (model KTPCA) was added and continued to stir for 5 minutes to obtain modified carbonaceous coal gangue mortar. The obtained mortar was poured into a test mold and vibrated on a vibration table for 60 seconds to remove air. The specimen was cured at room temperature.

[0032] Example 2 A modified carbonaceous coal gangue, the preparation of which comprises the following steps: Take 25kg of carbonaceous coal gangue for pretreatment, crush the carbonaceous coal gangue to a particle size of less than 4.75mm, screen, wash with water, put it into a blender and stir, add 2.25kg of water glass and 2kg of calcium sulfate in sequence, continue stirring for 10min, slowly add 7kg of modified polyvinyl acetate emulsion, keep stirring for 8min, mix well, and naturally dry to obtain modified carbonaceous coal gangue. The modified polyvinyl acetate emulsion used in this example is prepared in Preparation Example 1.

[0033] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in Example 1.

[0034] Example 3 A modified carbonaceous coal gangue, the preparation of which comprises the following steps: 30 kg of carbonaceous coal gangue was pretreated, crushed to a particle size of less than 4.75 mm, sieved, washed with water, and then put into a blender and stirred, 1.5 kg of water glass and 4 kg of calcium sulfate were added in sequence, and stirring was continued for 10 min, and then 6.5 kg of modified polyvinyl acetate emulsion was slowly added, stirring was maintained for 10 min, and after mixing evenly, the modified carbonaceous coal gangue was naturally dried. The modified polyvinyl acetate emulsion used in this embodiment was prepared in Preparation Example 1.

[0035] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0036] Example 4 A modified carbonaceous coal gangue, which is different from Example 1 in that the modified polyvinyl acetate emulsion used in this example is prepared in Preparation Example 2.

[0037] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0038] Example 5 A modified carbonaceous coal gangue, which is different from Example 1 in that the modified polyvinyl acetate emulsion used in this example is prepared in Preparation Example 3.

[0039] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0040] Example 6 A modified carbonaceous coal gangue, which is different from Example 1 in that the modified polyvinyl acetate emulsion used in this example is prepared in Preparation Example 4.

[0041] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0042] Example 7 A modified carbonaceous coal gangue, which is different from Example 1 in that the sulfate solution used in this example is a magnesium sulfate solution.

[0043] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0044] Example 8 A modified carbonaceous coal gangue, which is different from Example 1 in that this embodiment also includes 3 kg of fly ash, and the preparation includes the following steps: Take 20kg of carbonaceous coal gangue for pretreatment, crush the carbonaceous coal gangue to a particle size of less than 4.75mm, screen, wash with water, put it into a blender and stir, add 3kg of water glass and 3kg of calcium sulfate in sequence, continue stirring for 10min, add 3kg of fly ash and stir evenly, then slowly add 8kg of modified polyvinyl acetate emulsion, keep stirring for 5min, mix evenly, and naturally dry to obtain modified carbonaceous coal gangue. The modified polyvinyl acetate emulsion used in this example is prepared in Preparation Example 1.

[0045] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0046] Example 9 A modified carbonaceous coal gangue, which is different from Example 8 in that 5 kg of fly ash is added in this example.

[0047] A modified carbonaceous coal gangue is used in concrete. The modified carbonaceous coal gangue used is prepared in this embodiment, and the specific application is the same as that in embodiment 1.

[0048] Comparative Example Comparative Example 1 A modified carbonaceous coal gangue is different from Example 1 in that no modified polyvinyl acetate emulsion is added in this comparative example.

[0049] Comparative Example 2 A modified carbonaceous coal gangue is different from Example 1 in that unmodified polyvinyl acetate emulsion is used instead of modified polyvinyl acetate emulsion in this comparative example.

[0050] Comparative Example 2 A modified carbonaceous coal gangue is different from Example 1 in that water glass is not added in this comparative example.

[0051] Performance testing Test method / test method Mechanical properties: According to GB / T 17671-2021 "Test method for strength of cement mortar", 40mm×40mm×160mm mortar strips were used to test the compressive and flexural strength of concrete at 7d and 28d. The test results are shown in Table 1; Table 1 Test results Combining Examples 1-3 and Comparative Examples 1-2 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Examples 1-2, indicating that the addition of modified polyvinyl acetate emulsion can be tightly combined with the surface of coal gangue, fill the pores and defects in the carbonaceous coal gangue, enhance the strength of the modified carbonaceous coal gangue, and thus enhance the mechanical properties of concrete made from the modified coal gangue.

[0052] Combining Examples 1-3 and Comparative Example 3 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3, indicating that the addition of water glass is conducive to reacting with coal gangue, and sodium silicate reacts chemically with silicon and aluminum oxides in carbonaceous coal gangue to generate aluminosilicate gel, which has strong adhesion and filling properties, can fill the pores and cracks in the coal gangue, improve the density and strength of carbonaceous coal gangue, and thus improve the mechanical properties of carbonaceous coal gangue concrete.

[0053] It can be seen from Examples 1-6 and Table 1 that the experimental data of Example 6 are better than those of Examples 1-5, indicating that the use of hydrogen peroxide as an initiator in the preparation of polyvinyl acetate emulsion is beneficial to help vinyl acetate undergo polymerization to generate polyvinyl acetate emulsion with a narrow molecular weight distribution. The polyvinyl acetate emulsion with a narrow molecular weight distribution has a more uniform molecular size, so that the emulsion can penetrate into the tiny pores and cracks of the coal gangue more evenly, thereby more effectively filling the pores of the coal gangue and improving the density and overall strength of the coal gangue.

[0054] Combining Example 1 with Example 7, it can be seen that the performance of the concrete prepared in Example 1 and Example 7 is not much different, indicating that the use of either magnesium sulfate or sodium sulfate can play a good stimulating role, stimulate the reaction between water glass and coal gangue, promote the formation of aluminosilicate gel, and is beneficial to improving the strength of carbonaceous coal gangue.

[0055] Combining Example 1 with Examples 8-9, it can be seen that the experimental data of Examples 8-9 are better than those of Example 1, indicating that adding active powder during the modification process of coal gangue is beneficial to adsorb on the surface of coal gangue and improve the strength of coal gangue as aggregate. At the same time, the active powder has good reactivity. When carbonaceous coal gangue is used in concrete, it can help improve the interaction with other raw materials and improve its mechanical properties.

[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A modified carbonaceous coal gangue, characterized in that: The composition comprises the following raw materials in parts by weight: 1.5-3 parts of water glass, 5-8 parts of modified polyvinyl acetate emulsion, 20-30 parts of carbonaceous coal gangue, and 2-4 parts of sulfate solution. The modified polyvinyl acetate emulsion is obtained by copolymerization and modification of methyl methacrylate and vinyl acetate emulsion.

2. The modified carbonaceous coal gangue according to claim 1, characterized in that: The modified polyvinyl acetate emulsion is prepared by the following steps: Vinyl acetate, methanol, initiator and emulsifier are added in sequence and stirred evenly at room temperature. After heating to 60-70°C, methyl methacrylate is added. Polymerization reaction is carried out at normal pressure for 1-2 hours. The product is taken out and distilled to remove methanol to obtain modified polyvinyl acetate emulsion.

3. The modified carbonaceous coal gangue according to claim 2, characterized in that: In the preparation process of the modified polyvinyl acetate emulsion, the weight proportion of vinyl acetate, methyl methacrylate, emulsifier and initiator added is 2-4:1:0.2:0.3-0.

5.

4. The modified carbonaceous coal gangue according to claim 1, characterized in that: The initiator is hydrogen peroxide.

5. The modified carbonaceous coal gangue according to claim 1, characterized in that: The sulfate solution is any one of calcium sulfate and magnesium sulfate solution.

6. The modified carbonaceous coal gangue according to claim 1, characterized in that: The raw materials also include 3-5 parts of active powder, which is any one of fly ash, limestone powder and silica fume.

7. A method for preparing modified carbonaceous coal gangue according to any one of claims 1 to 3, characterized in that: The steps include: The carbonaceous coal gangue is pretreated, crushed, screened and cleaned, and then water glass and sulfate solution are added in sequence while stirring. After continuing to stir for 5-10 minutes, the modified polyvinyl acetate emulsion is slowly added, stirred and mixed evenly, and then dried to obtain the modified carbonaceous coal gangue.

8. Use of the modified carbonaceous coal gangue according to any one of claims 1 to 6 in concrete.

Citation Information

Patent Citations

  • Regenerated aggregate concrete and preparation method thereof

    CN110845184A

  • Dry-mixed mortar and preparation method thereof

    CN114790099A

  • High-performance environment-friendly concrete for shield segment production and preparation method thereof

    CN115838265A

  • High-crack-resistance concrete and preparation method thereof

    CN116730680A

  • Bi-component magnesium phosphate cement-based anchoring agent and use method thereof

    CN118063185A